2017
DOI: 10.1177/1010428317691429
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 regulates glutamine metabolism in glioblastoma through targeting glutaminase

Abstract: Glioblastoma is the most aggressive manifestation of malignant gliomas and considered to be among the deadliest forms of human cancers. MicroRNAs are found to tightly regulate diverse biological processes and considered to play important roles in cancer etiology. In this study, we found that microRNA-153 was significantly downregulated in glioblastoma tissues compared to matched non-tumor tissues and in glioblastoma cell lines. To investigate the potential function of microRNA-153 in glioblastoma, we transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…miRNAs are key molecules for post-transcriptional regulation [ 34 ], and are promising candidates in the regulation of paics and atic . Indeed, several miRNAs have been shown to regulate glutamine metabolism through targeting glutaminase expression [ 27 , 52 , 66 ] and may thereby affect the purine biosynthesis pathway genes. In our study, we have identified the miRNA dre-mir-2192 as being differentially expressed in fdx1b −/− mutants.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are key molecules for post-transcriptional regulation [ 34 ], and are promising candidates in the regulation of paics and atic . Indeed, several miRNAs have been shown to regulate glutamine metabolism through targeting glutaminase expression [ 27 , 52 , 66 ] and may thereby affect the purine biosynthesis pathway genes. In our study, we have identified the miRNA dre-mir-2192 as being differentially expressed in fdx1b −/− mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when GLS was ectopically overexpressed, the effect of miR-153 on GLS was abrogated, due to the absence of a 3'UTR in the exogenous GLS transcript. Interestingly, a negative correlation between GLS and miR-153 expression was observed in samples of glioblastoma, suggesting that miR-153 regulates glutamine metabolism in this type of cancer [113].…”
Section: Mir-153mentioning
confidence: 98%
“…Another miRNA reported to regulate GLS protein expression is miR-203, which additionally sensitizes malignant melanoma cells to temozolomide chemotherapy (109). Expression of glutamate cysteine ligase, the rate limiting enzyme of glutathione (GSH) synthesis, is attenuated by miR-18a in liver cancer (110) and by miRNA-153 in glioblastoma (111). Additionally, miR-450a limits the metastatic potential of ovarian cancer cells by targeting a set of mitochondrial mRNAs to reduce glycolysis and glutaminolysis (112).…”
Section: Mirnas Involved In Glutamine Metabolismmentioning
confidence: 99%